2021
DOI: 10.35484/pssr.2021(5-ii)88
|View full text |Cite
|
Sign up to set email alerts
|

Suffering Silence and Turnover Intentions while Exposed to Workplace Bullying: The Role of Psychological Distress

Abstract: Although workplace bullying is a well-focused phenomenon in the Western context but the specific way it unfolds in nonwestern countries and especially in their higher education sector remains largely unexposed. In response to this gap, an empirical inquiry has been conducted across higher education institutions in Pakistan. This paper not only improves our understanding of the scope and features of bullying in HEI but also proposes strategies sufferers could employ to deal with the workplace bullying. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ferguson (2012) found that workplace bullying, characterized by rudeness and unpleasant behavior from subordinates and peers, contributes to PD, leading to reduced employee performance. Previous studies have shown a positive association between WB and PD (Attell et al, 2017;Bhatti and Ahmed, 2021). Moreover, more frequent incidents of bullying have been found to lead to greater distress among nurses (Berry et al, 2016).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 89%
See 1 more Smart Citation
“…Ferguson (2012) found that workplace bullying, characterized by rudeness and unpleasant behavior from subordinates and peers, contributes to PD, leading to reduced employee performance. Previous studies have shown a positive association between WB and PD (Attell et al, 2017;Bhatti and Ahmed, 2021). Moreover, more frequent incidents of bullying have been found to lead to greater distress among nurses (Berry et al, 2016).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 89%
“…Although WB indirectly affects employee performance, it directly influences employee behavior (Anasori et al , 2020). The stress caused by WB further deteriorates performance in the workplace (Bhatti and Ahmed, 2021). Khalique et al (2018) argue that WB negatively impacts the productivity of peers and leads to a decrease in employee efficiency, consequently affecting organizational productivity.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Peers might be requested to accept the obligation that the harassed person show silent behavior for the extra work. It becomes a practice when more than one employee is usually engaged in this phase; the estimates of turnover costs are also increased [73]. Previous study evidence showed that workplace silence behavior is positively linked to turnover intentions or workers who intend to leave work [52].…”
Section: -3-employee Silence and Turnover Intentionmentioning
confidence: 99%